Strategi Bauran Pemasaran Produk Kredit Usaha Rakyat terhadap Minat Nasabah pada Bank Syariah Indonesia KC Suniaraja - Sinta Widia Ningsih; Lulu Madaniah; Gunardi Gunardi (Ekonomis: Journal of Economics and Business, 2022)
The purpose of this study is to analyze the influence of the marketing mix, including product, price, place, promotion, employee, and process, as well as physical evidence of customer interest in the People's Business Credit product at Bank Syariah Indonesia KC Bandung Suniaraja simultaneously or partially. The population that the researcher used in this study is KUR customers at Bank Syariah Indonesia KC Suniaraja. In addition, the analytical methods used in this study are the descriptive analysis method and the multiple regression analysis method using SPSS 26. The data collection technique for this study was used by distributing questionnaires, which resulted in 80 respondents. The hypotheses tested were the T-Test and the F-Test. Based on the results of the study, it was proved that partially the product, place, promotion, process, and employees did not have an impact on customer interest, but price as well as physical evidence had an effect on customer interest. Simultaneously, all these variables have an impact on customer interest in choosing KUR products at Bank Syariah Indonesia KC Bandung Suniaraja.